log(x-2)-log(4-x)=1-log(13-x)

Simple and best practice solution for log(x-2)-log(4-x)=1-log(13-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for log(x-2)-log(4-x)=1-log(13-x) equation:


Simplifying
log(x + -2) + -1log(4 + -1x) = 1 + -1log(13 + -1x)

Reorder the terms:
glo(-2 + x) + -1log(4 + -1x) = 1 + -1log(13 + -1x)
(-2 * glo + x * glo) + -1log(4 + -1x) = 1 + -1log(13 + -1x)
(-2glo + glox) + -1log(4 + -1x) = 1 + -1log(13 + -1x)
-2glo + glox + (4 * -1glo + -1x * -1glo) = 1 + -1log(13 + -1x)
-2glo + glox + (-4glo + 1glox) = 1 + -1log(13 + -1x)

Reorder the terms:
-2glo + -4glo + glox + 1glox = 1 + -1log(13 + -1x)

Combine like terms: -2glo + -4glo = -6glo
-6glo + glox + 1glox = 1 + -1log(13 + -1x)

Combine like terms: glox + 1glox = 2glox
-6glo + 2glox = 1 + -1log(13 + -1x)
-6glo + 2glox = 1 + (13 * -1glo + -1x * -1glo)
-6glo + 2glox = 1 + (-13glo + 1glox)

Solving
-6glo + 2glox = 1 + -13glo + 1glox

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '13glo' to each side of the equation.
-6glo + 13glo + 2glox = 1 + -13glo + 13glo + 1glox

Combine like terms: -6glo + 13glo = 7glo
7glo + 2glox = 1 + -13glo + 13glo + 1glox

Combine like terms: -13glo + 13glo = 0
7glo + 2glox = 1 + 0 + 1glox
7glo + 2glox = 1 + 1glox

Add '-1glox' to each side of the equation.
7glo + 2glox + -1glox = 1 + 1glox + -1glox

Combine like terms: 2glox + -1glox = 1glox
7glo + 1glox = 1 + 1glox + -1glox

Combine like terms: 1glox + -1glox = 0
7glo + 1glox = 1 + 0
7glo + 1glox = 1

Reorder the terms:
-1 + 7glo + 1glox = 1 + -1

Combine like terms: 1 + -1 = 0
-1 + 7glo + 1glox = 0

The solution to this equation could not be determined.

See similar equations:

| 8x-12x^2=0 | | 2w^2+5w-44=0 | | 0.3(x+30)+1.5x=90 | | 10x+2y=03x+5y=33 | | 3a^3b^3-9a^2b^4= | | 2x-7=14-5x | | (4x-5)+(9x+2)=(4-6x)-(7x+8) | | 10x+2y=0 | | 5e^3x=19 | | 3+7p-2=9p+26-7p | | 3x^2-4xy+7y^2=13 | | -5(-8a-6)-(-4a+12)-6(2a-9)= | | x^3+2x^2-8x-48=0 | | x^3-2x^2-8x-48=0 | | 3/x+12x=0 | | 3a+2b=-2 | | -5x+9x=3+17 | | 6/2x=-2 | | 6-2xy=-2 | | 38-7x=2x+17 | | 4-5x=-19 | | 3x+5=-x | | 5-10=153-38x | | 5x-7y+31=0 | | -2t^3=60t-26t^2 | | 3x+10=-67+-8x | | 3x+10=67-8x | | x^2+8y-4z=134 | | 16t^2+5776=0 | | -16t^2+3600=0 | | 3(2x+2)-9=-33 | | (16+2x)(20+2x)=480 |

Equations solver categories